A transcriptomic atlas at bulk and single-cell levels identifies novel transcriptional and splicing regulators of ECM homeostasis in osteoarthritis - Ye, Xiguang; Zheng, Chunyan; Li, Hao (Frontiers in Genetics, 2025)
Osteoarthritis (OA) is a common chronic degenerative joint disease. Chondrocytes undergo dynamic changes during the pathogenesis of OA, and the destruction of the extracellular matrix (ECM) and its homeostatic disruption are hallmarks of OA. This study explores the roles of transcriptional and alternative splicing (AS) mechanisms in regulating extracellular matrix (ECM) homeostasis in osteoarthritis (OA), using bulk and single-cell RNA-sequencing data. By analyzing two OA transcriptome datasets, we identified differentially expressed genes (DEGs) that are enriched in ECM-related pathways and constructed a regulatory network between differentially expressed transcription factors (DE TFs) and ECM-related DEGs. This revealed the potential roles of transcription factors ELF3 and DDIT3 in regulating the expression of COL3A1, COL5A2, and S100A4. Single-cell RNA-sequencing data further validated the expression patterns of ELF3 and DDIT3 in distinct chondrocyte subtypes. Additionally, by analyzing AS events, we identified the RNA-binding protein (RBP) KHDRBS3 as a regulator of AS for the ECM-related gene IL16. Aberrant changes in these events may impact the ECM environment of chondrocytes and contribute to the pathogenesis of OA. This study, for the first time, dissects the regulatory models in OA cartilage at both transcriptional and post-transcriptional levels. These findings provide novel potential targets for early diagnosis and intervention strategies in OA.